2008
DOI: 10.1074/jbc.m800128200
|View full text |Cite
|
Sign up to set email alerts
|

Histone Code Modifications Repress Glucose Transporter 4 Expression in the Intrauterine Growth-restricted Offspring

Abstract: We examined transcriptional and epigenetic mechanism(s) behind diminished skeletal muscle GLUT4 mRNA in intrauterine growth-restricted (IUGR) female rat offspring. An increase in MEF2D (inhibitor) with a decline in MEF2A (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
156
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(160 citation statements)
references
References 66 publications
(95 reference statements)
3
156
0
1
Order By: Relevance
“…7 There is evidence showing that early exposure to suboptimal environment induces epigenetic changes predisposing to type 2 diabetes (Table 1). [22][23][24][25] In rats, the exposure to uteroplacental insufficiency induces hepatic DNA hypomethylation and histone hyperacetylation of histone H3 on lysine 9 (H3K9), lysine 14 (H3K14) and lysine 18 (H3K18) at birth 26 These changes persist up to day 21 of postnatal life, suggesting a permanent effect on hepatic gene expression. The hyperacetylation on histone H3 in the liver of IUGR rats occurs in association with decreased nuclear protein levels of histone deacetylase 1 (HDAC1) and HDAC activity.…”
Section: The Mechanisms Of Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…7 There is evidence showing that early exposure to suboptimal environment induces epigenetic changes predisposing to type 2 diabetes (Table 1). [22][23][24][25] In rats, the exposure to uteroplacental insufficiency induces hepatic DNA hypomethylation and histone hyperacetylation of histone H3 on lysine 9 (H3K9), lysine 14 (H3K14) and lysine 18 (H3K18) at birth 26 These changes persist up to day 21 of postnatal life, suggesting a permanent effect on hepatic gene expression. The hyperacetylation on histone H3 in the liver of IUGR rats occurs in association with decreased nuclear protein levels of histone deacetylase 1 (HDAC1) and HDAC activity.…”
Section: The Mechanisms Of Programmingmentioning
confidence: 99%
“…34 Interestingly, the subjects exposed to famine periconceptionally showed, 60 years later, decreased methylation of IGF-II, whereas no change in the degree of IGF-II methylation was observed in those exposed to famine late in gestation. 35 The reduced methylation of IGF-II may represent the 22 Liver CPT-I Rate-limiting transporter in mitochondrial fatty acid b-oxidation H3K9 hyperacetylation affecting association with gene promoter IUGR rats 23 Pancreatic islets PDX-1 Transcription factor critical for b-cell function and development H3 and H4 deacetylation, H3K4 demethylation, H3K9 methylation IUGR rats 24 Skeletal muscle GLUT4 Glucose transporter H3K14 de-acetylation; H3K9 methylation IUGR rats 25 Pancreatic islets CGH-1 Role in endothelial dysfunction and b-cell development CpG hypermethylation in intergenic sequences IUGR rats 25 Pancreatic islets FGFR-1 Fibroblast growth factor receptor CpG hypomethylation in intergenic sequences IUGR rats 25 Pancreatic islets PCSK-5 Role in peptide processing and maturation CpG hypermethylation in transcription start site Humans 35 Blood IGF-II Fetal growth CpG hypomethylation…”
Section: Evidence For Programmingmentioning
confidence: 99%
“…Progression of these histone modifications parallels the progressive decrease in Pdx-1 expression which locks in the silenced state in the IUGR adult pancreas resulting in diabetes (43) . Similarly, Raychaudhuri et al (44) demonstrated that perinatal nutrient restriction resulting in IUGR leads to histone modifications in skeletal muscle that directly decrease GLUT type 4 (Glut4) gene expression. This effectively creates a metabolic knockdown of this important regulator of peripheral glucose transport and insulin resistance, thereby contributing to adult type 2 diabetes (44) .…”
Section: Epigenetic Mechanisms Elicited By Maternal Diet During Pregnmentioning
confidence: 99%
“…A number of studies suggest that uteroplacental insufficiency, a common cause of IUGR, induces epigenetic modifications in offspring (97)(98)(99)(100) . Epigenetic modifications affecting processes important to glucose regulation and insulin secretion, characteristics essential to the pathophysiology of T2D have been described in the IUGR liver, pancreatic b-cells and muscle (97)(98)(99)(100) .…”
Section: Epigenetic Regulation Of Gene Expression In Fetal Growth Retmentioning
confidence: 99%
“…Epigenetic modifications affecting processes important to glucose regulation and insulin secretion, characteristics essential to the pathophysiology of T2D have been described in the IUGR liver, pancreatic b-cells and muscle (97)(98)(99)(100) .…”
Section: Epigenetic Regulation Of Gene Expression In Fetal Growth Retmentioning
confidence: 99%